Evaluation of soil toxicity using different biotests on Pisum sativum: a case study. (3rd September 2018) - Massa, N.; Cesaro, P.; Todeschini, V.; Bona, E.; Cantamessa, S.; Berta, G.
Abstract: In this study we used Pisum sativum as model plant, to perform a battery of plant biotests, based on the analysis of biological endpoints, ranging from the macroscopical to the microscopical level, in order to evaluate the toxicity of soils sampled from three different polluted areas (two industrial and one exposed to heavy vehicular traffic). In addition to the conventional germination tests and early root growth analyses, the mitotic index and the percentages of mitotic phases and of aberrations in the root apices were calculated. Moreover, DNA loss and damage were evaluated by flow cytometry and COMET assay, respectively. Root samples from polluted soils showed lower mitotic indices and a higher mitotic aberration percentage and DNA loss in comparison to the controls. Data obtained by COMET tests highlighted the soil genotoxicity, especially in the two industrial areas. All together, our results showed that the three studied sites were characterised by different levels of toxicity: in particular, one of the two industrial sites was the most harmful.